Analysis of Writing Error in Teaching Writing Skills to Class four Student at SD Jam’iyyatul Hujjaj Bukittinggi - Mulyani Maiza; Nurhasnah Nurhasnah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The purpose of this study is to find out the mistakes in writing Arabic vocabulary and the solutions to these mistakes. And the research methodology used by researchers is descriptive qualitative research, because researchers analyze facts in general by presenting existing facts to form new ideas based on the research reality. And data collection methods in this study are observation and documentation. And the results in writing Arabic vocabulary in learning writing skills that the researchers got in grade 4 SD Jam'iyyatul hujjaj Bukittinggi: Errors in writing Arabic vocabulary according to the rules as many as 25 students. errors in differentiating the writing of Arabic letters such as: ت،ط،ذ،ز،س،ش،ص،ض as many as 18 students. And errors in the difficulty of writing vowel dhommah as many as 16 students. errors in differentiating writing between tactic and ta marbuthah as many as 20 students. errors in distinguishing short length as many as 25 students. There are many solutions to errors in writing Arabic words, including providing more exposure for students in video or image form to professional writing.